A COLLABORATION MODEL BETWEEN NURSING EDUCATION INSTITUTIONS AND CORECTIONAL INSTITUTIONS IN AN EFFORT TO MINIMIZE HEALTH PROBLEMS OF INMATES - Wilma Wilma; Ayu Lestari; Imam Zainuri; Utari Christya Wardhani (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2026)
Background: Correctional institutions represent a unique healthcare setting that remains underutilized as a learning platform in nursing education. Despite the obligation to uphold inmates’ health rights and meet healthcare service standards, the Indonesian correctional system continues to face significant challenges in addressing health problems among incarcerated populations. Strengthening collaboration between nursing educational institutions and correctional facilities may offer a strategic approach to improving healthcare access and outcomes in this high-risk and marginalized group.Objective: This study aimed to develop a collaboration model between nursing educational institutions and correctional institutions to minimize health problems among inmates while enhancing nursing education and student competencies.Methods: This study employed a mixed qualitative–quantitative design conducted in two stages. The first stage involved exploring best practices through in-depth interviews. The second stage focused on developing a collaboration model using the Delphi technique to achieve expert consensus. A total of 21 participants were recruited using purposive sampling, including prison healthcare coordinators, correctional nurses, nursing lecturers, and students involved in collaborative programs. Data from the qualitative phase were analyzed using thematic analysis, while the Delphi process was used to refine and validate the model, achieving a consensus level of greater than 70%.Results: The study resulted in a comprehensive collaboration model comprising three main domains. The personal system includes perception, commitment, and empathy; the interpersonal system includes communication, roles, and role modeling; and the social system includes policies, procedures, and security considerations. This model reflects a multidimensional framework for effective collaboration between educational and correctional institutions.Conclusions: The proposed collaboration model provides a structured approach to improving healthcare access and quality for inmates while simultaneously enhancing experiential learning opportunities for nursing students. Effective implementation of this model has the potential to strengthen health outcomes in correctional settings and contribute to the development of competent, socially responsive nursing professionals